LAPANGAN PUPUTAN BADUNG SEBAGAI RUANG KREATIF PUBLIK BAGI PENGEMBANGAN KOTA KREATIF DENPASAR - , MADE BHELA SANJI BUANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The creative city oriented on improving the quality of human resources. The challenge is how to realize an attractive urban space and inspiring creativity in the city. One of the pre-conditions in the creative city is the availability of creative space as a place to interact, recreation, looking for inspiration and creative activity itself. Denpasar city who want to lead a creative cities also should pay attention to this.Lapangan Puputan Badunghave strategic position potentially become a creative space. This study was conducted to verify the creative aspects of public space at Lapangan Puputan Badung. This research uses a deductive approach, which is using the theoretical framework in the form of the creative aspects of public space which is then verified in the field. The data used in the form of quantitative supported with qualitative descriptions . Data retrieval through the deployment of a number of sample research questionnaires, which amounted to 105 respondents . Analyzed using descriptive statistics and analysis factors using principle component analysis (PCA) . The results are Lapangan Puputan Badung were occupied the creative aspects of public space, namely comfort, openness, accessibility, tolerance and diversity. The main factors of interest to visitors in the creative aspects of public space are: ( 1 ) support facilities of comfort and security, (2 ) the diversity of activities and facilities ,(3 ) ease of access, (4 ) freedom of expression, ( 5 ) clarity of location, parking lot, trees